2017
DOI: 10.1016/j.jplph.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine slows down the breakdown of storage lipid and degradation of autophagic bodies in sugar-starved embryo axes of germinating lupin seeds

Abstract: The research was conducted on embryo axes of yellow lupin (Lupinus luteus L.), white lupin (Lupinus albus L.) and Andean lupin (Lupinus mutabilis Sweet), which were isolated from imbibed seeds and cultured for 96h in vitro under different conditions of carbon and nitrogen nutrition. Isolated embryo axes were fed with 60mM sucrose or were sugar-starved. The effect of 35mM asparagine (a central amino acid in the metabolism of germinating lupin seeds) and 35mM nitrate (used as an inorganic kind of nitrogen) on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 50 publications
3
37
0
Order By: Relevance
“…Among them were peroxisomes. Such results support another hypothesis that in sugar-starved lupin embryo axes, pexophagy (a special kind of autophagy during which the peroxisomes are selectively degraded) can occur (Borek et al 2013c).…”
Section: Regulation Of Storage Lipid Breakdown In Germinating Lupin Ssupporting
confidence: 86%
“…Among them were peroxisomes. Such results support another hypothesis that in sugar-starved lupin embryo axes, pexophagy (a special kind of autophagy during which the peroxisomes are selectively degraded) can occur (Borek et al 2013c).…”
Section: Regulation Of Storage Lipid Breakdown In Germinating Lupin Ssupporting
confidence: 86%
“…So far in plants, it has only been observed that the degradation of the autophagic body is clearly inhibited by asparagine during sugar starvation-induced autophagy in cells of lupin (Lupinus spp.) embryo axes during seed germination [133]. Enhanced autophagy was found in sugar-starved cells of lupin embryo axes, which was evidenced, among other things, by a high degree of vacuolization and a clear decrease in phosphatidylcholine content [133,138,139].…”
Section: Regulation Of Autophagic Body Degradationmentioning
confidence: 96%
“…embryo axes during seed germination [133]. Enhanced autophagy was found in sugar-starved cells of lupin embryo axes, which was evidenced, among other things, by a high degree of vacuolization and a clear decrease in phosphatidylcholine content [133,138,139]. Under such conditions, the autophagic bodies were rapidly degraded and they were not observed in the enlarged vacuoles.…”
Section: Regulation Of Autophagic Body Degradationmentioning
confidence: 99%
See 2 more Smart Citations